Paternal energetic investments in copepods. (21st December 2015) - Bjærke, Oda; Andersen, Tom; Bækkedal, Kjersti S.; Nordbotten, Marius; Skau, Lars F.; Titelman, Josefin
Abstract: Copepod mating is a complex behavioral interplay between males and females. But successful mating also requires a physiological component in terms of egg‐ and spermatophore production. In striking contrast to the extensive literature on copepod egg production, costs of spermatophore production has largely been ignored. This article explores the energetic demands in male copepod reproduction, testing how food and predation risk influence spermatophore production. Moreover, we analyse swimming behavior to test if predation risk and food act on reproductive investments via behavioral responses. We found that spermatophore production depends strongly on food availability. The copepods increased grazing rates with predation risk when food was limited, and video analyses revealed that males spend less time swimming in presence of a risk cue. A review of the few available spermatophore production rates suggests that food limits spermatophore production for copepods at large. Apparently, potential encounter rates with mates or predators did not influence spermatophore production. However, the reduced activity indicates a trade‐off between risk avoidance and mate encounter, potentially influencing mating rates. This study shows that males invest considerable resources in each spermatophore, with implications for mating strategies and population dynamics in copepods, the most abundant metazoans on earth.